Pengaruh Penerapan Kurikulum Merdeka terhadap Hasil Belajar Mata Pelajaran Fiqih Siswa Kelas X di Madrasah Aliyah Mambaul Ulum Megaluh Jombang - Latifah, Novitri Lailatul; Waslah, Waslah; Alaul Huda, Saihul Atho (Lembaga Yasin AlSys, 2025)
This study is motivated by the challenges encountered in implementing the Kurikulum Merdeka, particularly in Fiqih instruction, which integrates the cognitive, affective, and psychomotor domains in a holistic manner. The objective of this study is to examine the implementation of the Kurikulum Merdeka in Fiqih learning for Grade X at MA Mambaul Ulum Megaluh Jombang and to analyze its impact on students’ academic achievement. A descriptive-correlational quantitative approach was employed using a total sampling technique. The research instrument consisted of a Likert-scale questionnaire that underwent validity and reliability testing, with 18 out of 20 items deemed valid and a Cronbach’s Alpha score of 0.819. The analysis results indicate a significant influence of Kurikulum Merdeka implementation on student learning outcomes, with a significance value of 0.024 (< 0.05). Assumption tests confirmed that the data were normally distributed, homogeneous, and linear. The study concludes that Kurikulum Merdeka positively contributes to the quality of Fiqih learning through contextual, differentiated, and project-based approaches. The findings imply the need for strengthened implementation strategies for Kurikulum Merdeka in religious education subjects, as well as further research using broader experimental designs to gain a deeper understanding.